Analysis of Results of Specific IgE in 100 Atopic Dermatitis Patients with the Use of Multiplex Examination ALEX2-Allergy Explorer - Čelakovská, Jarmila; Bukač, Josef; Cermákova, Eva; Vaňková, Radka; Skalská, Hana; Krejsek, Jan; Andrýs, Ctirad (International journal of molecular sciences, 2021)
BACKGROUND AND AIM: Progress in laboratory diagnostics of IgE-mediated allergy is the use of component-resolved diagnosis. Our study analyses the results of specific IgE to 295 allergen reagents (117 allergenic extracts and 178 molecular components) in patients suffering from atopic dermatitis (AD) with the use of ALEX2 Allergy Explorer. METHOD: The complete dermatological and allergological examination, including the examination of the sensitization to molecular components with ALEX2 Allergy Explorer testing, was performed. The statistical analysis of results was performed with these methods: TURF (total unduplicated reach and frequency), best reach and frequency by group size, two-sided tests, Fisher's exact test, and chi-square test (at an expected minimum frequency of at least 5). RESULTS: Altogether, 100 atopic dermatitis patients were examined: 48 men, 52 women, the average age 40.9 years, min. age 14 years, max. age 67 years. The high and very high level of specific IgE was reached in 75.0% of patients to 18 molecular components: from PR-10 proteins (Aln g 1, Bet v 1, Cor a1.0103, Cor a1.0401, Fag s 1), lipocalin (Can f 1), NPC2 family (Der f 2, Der p 2), uteroglobin (Fel d 1), from Alternaria alternata (Alt a 1), Beta expansin (Lol p 1, Phl p 1), molecular components from Timothy, cultivated rye (Secc pollen) and peritrophin-like protein domain Der p 23. The high and very high level of specific IgE to other lipocalins (Fel d 7, Can f 4), to arginine kinase (Bla g 9, German cockroach), and to allergen extracts Art v (mugwort), and Cyn d (Bermuda grass) reached 52.0% of patients. The severity of AD is in significant relation to the sensitization to molecular components of storage mites (Gly d 2, Lep d 2-NPC2 family), lipocalins (Can f 1, Can f 2, Can f 4, and Can f 6), arginine kinase (Asp f 6, Bla g 9, Der p 20, Pen m 2), uteroglobin (Fel d 1, Ory c 3), Mn superoxide dismutase (Mala s 11), PR-10 proteins (Fag s 1, Mal d 1, Cor a 1.0401, Cor a 1.0103), molecular components of the peritrophin-like domain (Der p 21, Der p 23), and to Secc pollen. In the subgroup of patients suffering from bronchial asthma, the significant role play molecular components from house dust mites and storage mites (Lep d 2, Der p 2, Der f 2-NPC2 family), cysteine protease (Der p 1), peritrophin-like protein domain (Der p 21, Der p 23), enolase from Alternaria alternata (Alt a 6), and Beta expansin Phl p 1. CONCLUSION: The results of our study demonstrate the detailed profile of sensitization to allergens reagents (allergen extract and molecular components) in patients with atopic dermatitis. We show the significance of disturbed epidermal barrier, resulting in increased penetration of allergens. We confirmed the significant relationship between the severity of AD, the occurrence of bronchial asthma and allergic rhinitis, and high levels of specific IgE to allergen reagents. Our results may be important for regime measures and immunotherapy; Der p 23 shall be considered as an essential component for the diagnosis and specific immunotherapy of house dust mite allergy.
Keywords: Dermatitis, Atopic; Asthma; bronchiální astma; Humans; imunoglobulin E; molecular components; lidé středního věku; Allergens; allergic rhinitis; Female; Aged; atopic dermatitis; dospělí; Pyroglyphidae; severity of atopic dermatitis; senioři; alergeny; lidé; zvířata; asthma bronchiale; Rhinitis, Allergic; Skin Tests; kožní testy; ALEX2 Allergy Explorer; alergická rýma; Adult; ženské pohlaví; Immunoglobulin E; Male; Middle Aged; Pollen; Adolescent; Czech Republic; atopická dermatitida; pyl; Animals; Česká republika; mužské pohlaví; disturbed epidermal barrier; mladiství